Peran Kepemimpinan dalam Meningkatkan Kinerja Pegawai Pada Kantor Urusan Agama di Kecamatan Salaman Magelang - Kusrianti, Rinda; Purwanto, Purwanto; Syarifah, Laili; Sholikhun, Muhamad (Pascasarjana STIE Amkop Makassar, 2024)
The Salaman District Religious Affairs Office (KUA) is a leading agency with a primary and strategic position within the Ministry of Religion because it deals directly with the community in providing services in the field of religious affairs as a place for technical services. To provide maximum service, the performance of KUA employees is a factor that needs special attention. Various factors influence employee performance, and one of them is the leadership factor. This research aims to analyse the role of leadership in improving employee performance and analyse what obstacles to improving employee performance there are. The type of research used is field research using a qualitative descriptive approach. Research data was collected through interviews and observations. Interviews were conducted with the Head of KUA and Staff and Extension Officers at KUA Salaman District, Magelang. After the data is collected, data analysis is then carried out. Data analysis uses an interactive model consisting of data collection, reduction, verification, and conclusion. This research concludes that effective leadership is about giving orders and creating a work environment that facilitates growth, engagement, and productivity. The five leadership functions carried out by the Head of the Salam District KUA create a solid foundation for improving employee performance, proving that a holistic and diverse approach to leadership can provide a sustainable positive impact in the organizational context. This research found that two main obstacles contributed to the challenge of improving the performance of Salaman District KUA employees: differences in educational backgrounds and limited facilities and infrastructure.